Digitalization, Convergence and The Film Industry - Misra, Gaurav (2009)
This research examines the strategic direction of firms in the film industry which are posed with challenges of growth and sustainability in a dynamically changing environment which is an outcome of rapid industry convergence fuelled by technological advancements which span the last decade. With an ongoing initiative within the industry which is aimed at digital migration, influx of internet, communications and other related industries which could possibly alter the course of strategy formulation at organizational level. This research attempts at studying a set of diverse literature on strategy and further relating it to firms in practice. This research utilises qualitative means of gathering data which are both; primary and secondary in nature. The collated data is further subject to analysis using the Porters’ Five Forces in order to understand the current and the anticipated climate while an industry level analysis stresses on the nature of firm’s growth patterns and resource set allocations within the industry. The secondary data set is analysed to gain an insight into the digital migration timeframe which aides the research in drawing out future course of strategic formulation. The Five Forces framework reveals a shift in bargaining power of firms at different levels while the industry level analysis indicates growth patterns in current and future integration efforts both; horizontal and vertical. The third set of analysis focuses on value chain disintermediation which is informed by Porters’ Five Forces and Industry level analysis. The threat to auxiliary businesses is highlighted by this analysis. Different strategic choices with firms are discussed with relevance to the findings, current industry composition, growth patterns and finally the new digital paradigm which the industry awaits.